2012
DOI: 10.1515/ijdhd-2011-0019
|View full text |Cite
|
Sign up to set email alerts
|

Socio-demographic and family correlates of hopelessness among adolescents in Shanghai, China

Abstract: Chinese secondary school students (n = 3022) responded to measures of adolescent hopelessness, perceived parental behavioral control, parental psychological control, and parentchild relational qualities. Results show that roughly one-fi fth of the Chinese adolescents displayed signs of hopelessness. Adolescent hopelessness was positively related to age, and boys displayed a lower level of hopelessness than did girls. Adolescent hopelessness was also related to parental education, marital status of the parents,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
4
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 19 publications
0
4
0
Order By: Relevance
“…Hopelessness can be defined as a trans-diagnostic psychological construct characterized by rigid and persistently negative expectations about the future and helplessness to change future outcomes [ 19 ]. It is associated with psychosocial risk factors, psychopathology and high-risk behaviors, such as deficit in cognitive development [ 20 ], negative inferential style [ 21 ], low socio-economic status [ 22 ], stress [ 23 ], emotional abuse [ 24 ], more severe depressive symptoms, suicidal ideation, substance abuse, aggression and violent behaviors [ 21 ].…”
Section: Introductionmentioning
confidence: 99%
“…Hopelessness can be defined as a trans-diagnostic psychological construct characterized by rigid and persistently negative expectations about the future and helplessness to change future outcomes [ 19 ]. It is associated with psychosocial risk factors, psychopathology and high-risk behaviors, such as deficit in cognitive development [ 20 ], negative inferential style [ 21 ], low socio-economic status [ 22 ], stress [ 23 ], emotional abuse [ 24 ], more severe depressive symptoms, suicidal ideation, substance abuse, aggression and violent behaviors [ 21 ].…”
Section: Introductionmentioning
confidence: 99%
“…There is considerable evidence that cognitive vulnerabilities, such as a negative inferential style, increase the likelihood of developing hopelessness (Abela et al 2009; Becker-Weidman et al 2009). Other environmental factors, such as low socio-economic status (Han and Shek 2012; Landis et al 2007), stress (LaFromboise et al 2010; Stein et al 2012), or emotional abuse (Courtney et al 2008) also increase the likelihood of becoming hopeless. Evidence of gender differences in levels of hopelessness is mixed; while many studies indicate that females are more likely than males to experience hopelessness (Rodriguez-Naranjo and Cano 2016), others have shown males reporting on average higher scores (Bolland 2003; Lester 2015).…”
Section: Introductionmentioning
confidence: 99%
“…or reduce hopelessness directly. Protective familial factors include: increased parent-adolescent communication (Kwok et al 2010), greater parental warmth (Han and Shek 2012; Li et al 2016), stronger parent-adolescent connection (Kliewer et al 2001; Stoddard, Henly, et al 2011), family stability (Ivanova and Israel 2005) and family support and community support (Grano et al 2014). Familial support, however, may not be effective in highly uncertain and unstable situations (e.g., living in a refugee camp; Afifi et al 2013; Kolarcik et al 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Other studies with emerging adults reported that greater psychological control was associated with lower perceived competence to take on adult roles (Lindell et al 2017). In a series of studies, Shek and colleagues (Han and Shek 2012;Shek 2007;Shek and Lee 2005) demonstrated higher levels of adolescent hopelessness in the face of high psychological control from parents.…”
mentioning
confidence: 99%